2013
DOI: 10.1063/1.4816265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of hydrogen sensing with Pt/TiO2 Schottky diodes

Abstract: The dynamics of hydrogen sensing with nanoporous Pt/TiO2 Schottky barriers is studied by time-resolved electronic transport measurements. The development with time of the doping density, the average Schottky barrier height, and the built-in voltage are determined from current-voltage and capacitance-voltage characteristics. The current-voltage characteristics change from exponential towards Ohmic behavior as time proceeds. This is interpreted in terms of local areas that switch from diodic to Ohmic response du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 37 publications
4
51
0
Order By: Relevance
“…This was hypothesized to be due to high energy impact from the sputtering process creating interfacial states thus allowing it to act more as an Ohmic contact rather than a Schottky barrier. 150,151 This work also investigated the n + Si/Ti (or more probably n + Si/TiSi x /Ti) 152 interface and showed both theoretically and experimentally that at high Si dopants levels charge could tunnel through the barrier created by the Si -TiSi x Schottky barrier, whereas at low dopant densities charge could not tunnel through this barrier. This charge transport mechanism is well illustrated in Fig.…”
mentioning
confidence: 95%
“…This was hypothesized to be due to high energy impact from the sputtering process creating interfacial states thus allowing it to act more as an Ohmic contact rather than a Schottky barrier. 150,151 This work also investigated the n + Si/Ti (or more probably n + Si/TiSi x /Ti) 152 interface and showed both theoretically and experimentally that at high Si dopants levels charge could tunnel through the barrier created by the Si -TiSi x Schottky barrier, whereas at low dopant densities charge could not tunnel through this barrier. This charge transport mechanism is well illustrated in Fig.…”
mentioning
confidence: 95%
“…In Ref. [5], it has been shown that n d saturates after 20 min of hydrogen exposure at room temperature, but this evolution has not been measured at low temperatures where this DLTS trace was started. However, after this sweep has been recorded, the sample has been sufficiently long around room temperature to ensure saturation of n d .…”
Section: Experimental Results and Interpretationmentioning
confidence: 99%
“…Also, even small concentrations of hydrogen are known to embrittle highly relevant metals like steels (). Mesoporous or nanotubular titanium dioxide‐based devices have been shown to be extremely sensitive hydrogen sensors . Typically, a catalytic electrode like Pt or Pd covers a TiO2 film and a Schottky barrier is formed at the interface ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also a concept based on percolation transport through Pd cluster arrays with a resolution of 100 µm has been demonstrated [12,13]. Here, we present a hydrogen detector that combines submicrometer spatial resolution with the high sensitivity of the Pt/TiO 2 -system [14][15][16], and with the possibility of on-chip implementation by established lithographic techniques.…”
Section: Introductionmentioning
confidence: 99%